Vision Scenes British television and dance - Mccarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Dance on British television screens. Dance for the Camera revives the concept of dance as a "total art work". PALABRAS CLAVE: dance programmes TV, Bob Lockyer, dance and television.